ANALISIS STRATEGI KOMISI PEMILIHAN UMUM (KPU) JAWA TIMUR UNTUK MENINGKATKAN PARTISIPASI POLITIK MASYARAKAT DALAM MENGHADAPI PEMILU TAHUN 2024 - Rifansyah, Muhammad Ridho; Anisykurlillah, Rosyidatuzzahro (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2024)
ABSTRACT With the introduction of technology and information systems, this also has an impact on public institutions, especially the General Election Commission (KPU), which utilizes digital media as a means of carrying out communication and outreach strategies to increase people's political participation in the participation of community members in the 2024 General Election (Pemilu). In order to achieve successful community involvement, implementing a well-structured plan such as a management strategy is necessary. The role of the General Election Commission (KPU), especially the East Java Province KPU is guided by KPU Decree Number 10 of 2018 concerning Socialization, Voter Education, Community Participation in the Implementation of General Elections. The aim of this research is to analyze the strategy of the East Java General Election Commission (KPU) to increase public participation in facing the 2024 elections. The methodology used in this research is a qualitative research method with a descriptive method where the data collection process is in the form of interviews, observation, documentation and literature study obtained through articles, books, information and so on related to the topic being discussed. Based on the research findings, it can be seen that the strategy implemented by the East Java KPU can be said to have worked well, as evidenced by the existence of several agendas of socialization activities that have been carried out such as the Election Carnival, showing the film